Anti-proliferative activity of triterpenes isolated from Clinicanthus nutans on Hep-G2 liver cancer cells - Zakaria, Khairun Najwa; Amid, Azura; Zakaria, Zubaidah; Jamal, Parveen; Ismail, Azli (2019)
Problem statement: Clinicanthus nutans has been used by Malaysian since long time ago. It is used to treat many diseases including cancer. Many studies carried out on its crude extract but no clear report on the specific secondary metabolites responsible for its nature in treating selected diseases. Objective: This study aims to confirm the practice carried out by many people on the usage of Clinicanthus nutans in treating cancer. Methods: C. nutans leaves were extracted by methanol. Thin layer chromatography was used to identify the suitable solvent for fractions separation. The fractions were then separated at larger volume using gravity column chromatography. Each fraction was tested on its anti-proliferative activity on Hep-G2 liver cancer cells by MTT assay. The phytochemical screening was carried out to identify the bioactive compound based on qualitative analysis. Results: The fraction 2 (F2) of C. nutans showed the lowest IC50 value of 1.73 µg/ml against Hep-G2 cancer cells, and it is identified as triterpenes. Conclusion: The fraction F2 identified as triterpenes isolated from C. nutans has potential as an anti-proliferative agent against liver cancer.